COPYWRITING STYLE DAN STRUKTUR NASKAH RADIO - Winda Kustiawan; Anissa Rahmadhani; Nadya Syakilah; Novi Lestari; Rizqi Ramadhani Siregar; Tasya Salsabila (Lembaga Pengembangan Kinerja Dosen, 2022)
The technology of sending signals by way of modulation as well as electromagnetic radiation with waves that travel through the air and produce sound is the meaning of radio. In broadcasting, scripts and writing are needed so that they are pleasing to the ear and also structured. In the process of writing copywriting, Style is needed so that the advertisements shown on the radio can be absorbed by listeners and are moved to buy the product being advertised and cause an action. Because radio only relies on audio, the sentence structure must be precise and there is a script structure that is being discussed so that it is good. Using research methods sourced from books and the internet. The essence of Copywriting style and the structure of discussion scripts on radio is to hone writing and editing skills in radio scripts.